Thyroid and Islet Autoantibodies Predict Autoimmune Thyroid Disease at Type 1 Diabetes Diagnosis - Jonsdottir, Berglind; Larsson, Christer; Carlsson, Annelie; Forsander, Gun; Ivarsson, Sten Anders; Lernmark, Åke; Ludvigsson, Johnny; Marcus, Claude; Samuelsson, Ulf; Örtqvist, Eva; Larsson, Helena Elding (The journal of clinical endocrinology and metabolism, 2017)
Context:Screening of autoimmune thyroid disease in children with type 1 diabetes is important but varies between clinics.Objective:To determine the predictive value of thyroid autoantibodies, thyroid function, islet autoantibodies, and HLA-DQ at diagnosis of type 1 diabetes for autoimmune thyroid disease during follow-up.Setting:Forty-three Swedish pediatric endocrinology units.Design, Patients, and Main Outcome Measures:At diagnosis of type 1 diabetes, autoantibodies against thyroid peroxidase (TPOAb), thyroglobulin (TGAb), glutamic acid decarboxylase (GADA), insulin, insulinoma-associated protein-2, and 3 variants of zinc transporter 8 (ZnT8W/R/QA) HLA-DQA1-B1 genotypes and thyroid function were analyzed in 2433 children. After 5.1 to 9.5 years, information on thyroxine treatment was gathered from the Swedish National Board of Health and Welfare’s Prescribed Drug Register.Results:Thyroxine was prescribed to 6% of patients. In patients <5 years of age, female sex [hazard ratio (HR) = 4.60; P = 0.008] and GADA (HR = 5.80; P = 0.02) were predictors. In patients 5 to 10 years old, TPOAb (HR = 20.56; P < 0.0001), TGAb (HR = 3.40; P = 0.006), and thyroid-stimulating hormone (TSH) (HR = 3.64; P < 0.001) were predictors, whereas in 10 to 15 year olds, TPOAb (HR = 17.00; P < 0.001) and TSH (HR = 4.11; P < 0.001) predicted thyroxine prescription.Conclusion:In addition to TPOAb and TSH, GADA at diagnosis of type 1 diabetes is important for the prediction of autoimmune thyroid disease in children <5 years of age.We studied whether markers at type 1 diabetes diagnosis were predictive of later autoimmune thyroid disease. We found that TPOAb and TSH as well as GADA were predictive in girls ˂5 years old at diagnosis.